Causes and prevalence of antisocial behaviour among students with hearing impairment in Ibadan, Nigeria (2015)
This study examined the causes and prevalence of antisocial behaviour among secondary school students with hearing impairment in Ibadan, Nigeria. Descriptive survey research design was adopted to carry out the study. Purposive sampling technique was used to select 60 students with hearing impairment from Methodist Grammar School (Deaf Unit), Bodija, Ibadan and Ijokodo High School, Ijokodo, Ibadan, Students Antisocial Behaviour Questionnaire (r=.80) was used to collect data. The data collected were analyzed using descriptive statistics of frequency count and percentage. The common causes of antisocial behaviour as revealed by the study are: media influence, lack of counsellor in schools, ineffective school administration, peer influence, broken home and lack of parental care. The findings of the study showed that the most common antisocial behaviour exhibited by the participants are: examination malpractice, lateness, abortion, stealing, rape, cultism and rudeness. There should be home-school partnership in curbing antisocial behaviour among students with hearing impairment in Nigeria.